TINJAUAN HUKUM ISLAM TERHADAP ‎PERAN PEREMPUAN DALAM ‎MENINGKATKAN PEREKONOMIAN ‎KELUARGA SEBAGAI BURUH PABRIK SABUT ‎KELAPA - Saragih, Napsiah (UIN Sumatera Utara Medan, 2024)
Women who work outside the home in the public sphere have significant impacts on their families, yielding both positive and negative consequences as they juggle dual roles. Positively, working women demonstrate greater understanding of their own and their husband's work, contributing to better social and individual adjustments. The research addresses women's roles in enhancing family economics as coconut fiber factory workers in Punggulan Village, alongside an examination of Islamic law regarding their employment. The hard work of wives and housewives in such roles reflects their commitment to meeting family economic needs. In conclusion, these women engage in employment out of necessity to support their families due to insufficient husband's income, highlighting their crucial economic contribution. Their dual roles exemplify adaptation to economic challenges within the framework of Islamic principles, emphasizing the importance of their economic participation for family welfare.Keywords: Role, Women, Factory Workers, Economy